Magnetic Study of Cerium-Iron-Transition Metal Mixed Compounds - Thakur, A.N.; Singh, S.V.; Singh, U.P.; Yadav, S.K.; Maurya, K.C.; Vishwakarma, S.C.; Singh, O.P. (Asian Journal of Chemistry, 2010)
The compounds of cerium-iron-transition element mixed oxides of the type CeFeTO4 have been prepared by a solid-state reaction technique and characterized by XRD pattern. The molar magnetic susceptibility (χM) of the powdered sample has been reported in a wide temperature range (300 to 1100 K). All the materials show a typical ferrimagnetic nature. The slope of asymptotic line yields an average magneton number, which indicates that all the materials are perfectly ionic. The transition ions are Ce3+, Fe2+ and Fe3+ in CeFe2O4; Ce3+, Cr3+ and Fe2+ in CeFeCrO4; Ce3+, Mn3+ and Fe2+ ion CeFeMnO4 and Ce3+, Fe3+ and Co2+ in CeFeCoO4.